Young People, Wellbeing and Sustainable Arctic Communities - Stammler, Florian; Toivanen, Reetta (Routledge Research in Polar Regions, 2021)
Youth are usually not (yet) decision makers in politics or in business corporations, but the sustainability of Arctic settlements depends on whether or not youth envision such places as offering opportunities for a good future. This is the first multidisciplinary volume presenting original research on Arctic youth. This edited book presents the results of two research projects on youth wellbeing and senses of place in the Arctic region. The contributions are united by their focus on agency. Rather than seeing youth as vulnerable and possible victims of decisions by others, they illustrate the diverse avenues that youth pursue to achieve a good life in the Arctic.　The contributions also show which social, economic, political and legal conditions provide the best frame for youth agency in Arctic settlements.　　 Rather than portraying the Arctic as a resource frontier, a hotspot for climate change and a place where biodiversity and traditional Indigenous cultures are under threat, the book introduces the Arctic as a place for opportunities, the realization of life trajectories and young people's images of home.　Rooted in anthropology, the chapters also feature contributions from the fields of sociology, geography, sustainability science, legal studies and political science.　　 This book is intended for an audience interested in anthropology, political science, Arctic urban studies, youth studies, Arctic social sciences and humanities in general. It would attract those working on Arctic sustainability, wellbeing in the Arctic, Arctic demography and overall wellbeing of youth.